Тепловизионный мониторинг качества сварных соединений, полученных сваркой трением с перемешиванием - Рубцов В. Е. Валерий Евгеньевич; Руденский Г. Е. Геннадий Евгеньевич; Тарасов С. Ю. Сергей Юльевич; Колубаев Е. А. Евгений Александрович; Гнюсов С. Ф. Сергей Фёдорович; Васильев П. А. Павел Александрович; Бакшаев В. А. Владимир Александрович (2015, 2015)
Заглавие с экрана